The The Religiosity of Master’s Students in the IAT Program at UIN Sunan Kalijaga from William James’ Perspective - Annisa Rahma Nabila (PT. Student Rihlah Indonesia, 2026)
The religious development of postgraduate students has received limited scholarly attention, particularly regarding the interaction of academic and spiritual experiences within Islamic higher education. This study aims to analyze the religious development of Master’s students in the Quranic Studies and Tafsir program, Class D, at UIN Sunan Kalijaga Yogyakarta through the perspective of William James’ theory of religious experience. A qualitative phenomenological approach was employed to explore the lived religious experiences of students in academic, personal, and social contexts. Data were collected through in-depth interviews and observations involving eight purposively selected informants and analyzed thematically. The findings reveal two distinct patterns of religious development: four students experienced significant growth in religiosity, while the remaining four showed relatively stable religious orientations. These developmental processes were shaped by internal factors, including religious beliefs, personal reflection, and spiritual awareness, together with external factors, such as academic discussions, social interactions, and campus religious activities. The findings demonstrate that the dimensions of ineffability, noetic quality, and transiency proposed by William James are reflected in the religious experiences of the students, highlighting the transformative role of subjective spiritual encounters. The novelty of this study lies in its integration William James’ theory of religious experience in the context of Islamic postgraduate education offers a deeper understanding of graduate students’ religious development. These findings imply that Islamic higher education institutions should strengthen reflection-based learning, dialogical classrooms, and structured spiritual development programs to foster religious growth among students while contributing to the advancement of the psychology of religion literature within contemporary Islamic higher education.